Lateral retroperitoneal approach for the treatment of a recumbent silkworm-like paravertebral schwannoma in the lumbar spine: a case report - Su, Lanming; Liu, Wei; Zhang, Yingying; Li, Feng; Liu, Yuanqin; Wang, Ziyu (Frontiers in Oncology, 2025)
ObjectiveThis case report describes the surgical management of a recumbent silkworm-like paravertebral schwannoma in the lumbar spine resected via the lateral retroperitoneal approach.MethodsA lumbar paravertebral schwannoma resembling a “recumbent silkworm” was excised using the lateral retroperitoneal approach. Intraoperative measures included electrophysiological monitoring and insertion of a ureteral D-J stent to protect critical surrounding anatomical structures. Complete tumor resection was achieved without intraoperative complications. Follow-up demonstrated no tumor recurrence or postoperative complications.ResultsThe duration of surgery was 310 min, with an estimated blood loss of 50mL. The tumor resection rate was 100%. The patient was discharged 11 days after hospitalization. Postoperative histopathological examination confirmed the diagnosis of schwannoma. There were no postoperative complications. The patient ADL (Activities of Daily Living score did not decline compared with the preoperative levels. After one year of follow-up, no signs of tumor recurrence were observed.ConclusionParavertebral tumors located in the anterior and lateral aspects of the lumbar spine pose significant surgical challenges because of their complex position and morphology. Complete excision of such tumors via the lateral retroperitoneal approach is an optimal treatment strategy.